2015
DOI: 10.1002/jts.21984
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual Cycle Effects on Psychological Symptoms in Women With PTSD

Abstract: The menstrual cycle has been implicated as a sex-specific biological process influencing psychological symptoms across a variety of disorders. Limited research exists regarding the role of the menstrual cycle in psychological symptoms among women with posttraumatic stress disorder (PTSD). The current study examined the severity of a broad range of psychological symptoms in both the early follicular (Days 2-6) and midluteal (6-10 days postlutenizing hormone surge) phases of the menstrual cycle in a sample of tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 75 publications
(47 citation statements)
references
References 24 publications
5
41
0
1
Order By: Relevance
“…14 Further, women with PTSD report more severe psychological symptoms based on the phase of their menstrual cycle. 15 Consistent with this observation, female rodents also show more fear and anxiety-related behaviors in phases of their estrous cycle characterized by low estrogen levels, specifically the metestrous or diestrous phases. 1619 …”
Section: Introductionmentioning
confidence: 53%
“…14 Further, women with PTSD report more severe psychological symptoms based on the phase of their menstrual cycle. 15 Consistent with this observation, female rodents also show more fear and anxiety-related behaviors in phases of their estrous cycle characterized by low estrogen levels, specifically the metestrous or diestrous phases. 1619 …”
Section: Introductionmentioning
confidence: 53%
“…Forty‐seven women with histories of trauma exposure participated in the current study as part of a larger investigation of menstrual cycle effects on the psychophysiology and neurobiology of PTSD (Nillni et al, ; Pineles et al, ). Participants were recruited from a Veterans Affairs (VA) hospital and the surrounding community.…”
Section: Methodsmentioning
confidence: 99%
“…This is notable because there are several studies demonstrating impaired PPI in the luteal phase of the menstrual cycle (Jovanovic et al, ; Kumari et al, ; Swerdlow, Hartman, & Auerbach, ). Participants included in the current study completed several other psychophysiological tasks and self‐report measures as part of a larger investigation; menstrual phase effects were observed for mood and anxiety symptoms (Nillni et al, ), as well as retention of extinction learning (Pineles et al, ). Although nicotine withdrawal has been found to impair PPI and smoking to satisfaction has been found to enhance PPI in smokers (Della Casa, Hofer, Weiner, & Feldon, ; Kumari, Checkley, & Gray, ), only one study of PPI in PTSD assessed tobacco use (Vrana et al, ).…”
mentioning
confidence: 99%
“…A series of studies on a sample of trauma-exposed females have provided data on progesterone levels during specific menstrual phases and its associations with various aspects of fear learning (Nillni et al, 2015;Pineles et al, 2016aPineles et al, , 2016bPineles et al, , 2018. Using a PPI paradigm, one study found that greater progesterone levels (assayed from plasma) were significantly associated with increased PPI among trauma-exposed females in the early follicular phase (Pineles et al, 2016a).…”
Section: Human Research On Progesterone In Fear and Ptsdmentioning
confidence: 99%